2010
DOI: 10.1097/sla.0b013e3181d970e3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of A 19-Item Surgical Safety Checklist During Urgent Operations in A Global Patient Population

Abstract: Implementation of the checklist was associated with a greater than one-third reduction in complications among adult patients undergoing urgent noncardiac surgery in a diverse group of hospitals. Use of the WHO Surgical Safety Checklist in urgent operations is feasible and should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
299
1
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 406 publications
(323 citation statements)
references
References 7 publications
7
299
1
16
Order By: Relevance
“…For example, although pay-for-performance can improve quality, the type, amount, and timeliness of the incentives all affected the magnitude of the behavioral change and the potential benefit of the strategy. Second, most studies have selectively focused on only certain aspects of quality such as safety [22,31,75,76] and timeliness [12,52]. A complete evaluation of quality would require examination of all the elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although pay-for-performance can improve quality, the type, amount, and timeliness of the incentives all affected the magnitude of the behavioral change and the potential benefit of the strategy. Second, most studies have selectively focused on only certain aspects of quality such as safety [22,31,75,76] and timeliness [12,52]. A complete evaluation of quality would require examination of all the elements.…”
Section: Discussionmentioning
confidence: 99%
“…Checklists also enhanced processes of care such as appropriate use of prophylactic antibiotics to reduce surgical site infection [22]. Two studies showed substantial reduction in adverse events and mortality after introduction of surgical checklists for elective and urgent operations [31,76]. Until recently, the primary application of checklists was in the operative period.…”
Section: Do Safety Checklists Improve Quality Of Surgical Care?mentioning
confidence: 99%
“…These insights shall be utilized to further improve MEDo. Finally, the usage of best practice checklists represents an emerging and important aspect of everyday life in hospitals [38,39]. Following this, we plan to integrate corresponding results of dealing with paper-based checklists into MEDo.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was maintained even in urgent and emergency cases. 15 Over the last several years, further compelling evidence has shown the power of using perioperative checklists. In a large well-designed study of 7,580 patients in the Netherlands, a perioperative checklist was implemented throughout six Dutch hospitals with five other hospitals used as controls.…”
Section: What Is the Evidence?mentioning
confidence: 99%